Redox and biometal status in Wistar rats after subacute exposure to fluoride and selenium counter-effects - Radovanović Jelena; Antonijević Biljana; Baralić Katarina; Ćurčić Marijana; Đukić-Ćosić Danijela; Bulat Zorica; Javorac Dragana; Buha Đorđević Aleksandra; Kotur-Stevuljević Jelena; Sudar-Milovanović Emina; Antonijević Miljaković Evica; Beloica Miloš; et al. (Arhiv za Higijenu Rada i Toksikologiju, 2022)
This study aimed to investigate the effect of 150 mg/L sodium fluoride (NaF) on redox status parameters and essential metals [copper (Cu), iron (Fe), and zinc (Zn)] in the blood, liver, kidney, brain, and spleen of Wistar rats and to determine the protective potential of selenium (Se) against fluoride (F-) toxicity. Male Wistar rats were randomly distributed in groups of five (n=5) receiving tap water (control) or water with NaF 150 mg/L, NaF 150 mg/L + Se 1.5 mg/L, and Se 1.5 mg/L solutions ad libitum for 28 days. Fluorides caused an imbalance in the redox and biometal (Cu, Fe, and Zn) status, leading to high superoxide anion (O2 .-) and malondialdehyde (MDA) levels in the blood and brain and a drop in superoxide dismutase (SOD1) activity in the liver and its increase in the brain and kidneys. Se given with NaF improved MDA, SOD1, and O2 .- in the blood, brain, and kidneys, while alone it decreased SH group levels in the liver and kidney. Biometals both reduced and increased F- toxicity. Further research is needed before Se should be considered as a promising strategy for mitigating F- toxicity.